Immunogenetic factors that limit the HIV-1 infection in MSM from Medellín, Colombia (2022)
ABSTRACT: Background: HIV-1 infection still representing a major public health problem in most of the countries affected by the epidemic, and men who have sex with men (MSM) continue to shoulder a disproportionate HIV disease. In Colombia, the prevalence of HIV in the general population is 0.4% while the prevalence in MSM is 17%. Despite the natural course of HIV-1 infection, small populations of individuals have been identified that, although they are directly exposed to the virus repeatedly, do not present serologic or clinical evidence of the infection; these people are known to be exposed to HIV-1 but seronegative (HESN). The study of seronegative MSM with high-risk behaviors and the possible finding of HESN individuals in this population represents an important opportunity to better understand HIV-1 infection and immune response, to improve the current therapeutic and preventive intervention strategies. Methods and Results: This study aimed to compare the immunological profile of Colombian seronegative MSM with different risk sexual behaviors. In the first study phase, 92 MSM were recruited through a community-based approach, and the sociodemographic, sexual behavior and clinical data were collected by a structured survey and in-depth interviews. HIV test was made on all participants to know their serostatus. Participants were classified into three groups according to the number of sexual partners in the last three months (0-4, 5-10, and >10 sexual partners), to compare the sociodemographic conditions and sexual behaviors. Multivariate logistic regression was used to compare the groups and to explore the associated factors with condomless sexual practice. The average age was 27 years (Me=25, IQR 22-31). The majority of subjects identified themselves as homosexual (85.9%) and 14.1% as bisexual or pansexual; no participants identified as heterosexual. The overall HIV estimated prevalence was 4.3%, while the estimated prevalence for MSM with >10 sexual partners in the last three months was 14.8%. This last group showed higher average age (p=0.015), a higher percentage of subjects who have had sex with people living with HIV (p=0.011), and an increased frequency of previous sexually transmitted infections (p=0.014). Having condomless sex with casual partners was associated with the number of sexual partners in the last three months. The number of sexual partners in the last 3 months generates a 5% risk of not using a condom with casual partners (OR, 1.058; 95% CI, 1.00–1.11). In the second study phase, 60 seronegative MSM with lower and riskier sexual behaviors were selected to study their immunogenetic profiles. They were divided into two groups; the low-risk group (n=44) compound by MSM with ≤4 sexual partners in the last three months, and the high-risk group (n=16), formed by MSM with ≥14 sexual partners in the same period. All included MSM were not sex workers, neither showed the CCR5 ∆32 mutation in their homozygous state. They also remain negative for anti-HIV-1/2 antibodies and HIV-1 proviral DNA. The high-risk group presented a higher frequency of sexual partners throughout life (p<0.001); a major number of sexual partners in the three months before the inclusion of the study (p<0.001), more unprotected intercourses in the last three months (p=0.001) and more frequency of previous sexually transmitted infections (p<0.001). To explore the basal activation profile of CD4+ and CD8+ T cells, the percentage of cells expressing CD38, HLA-DR, CD69, and Ki-67 molecules was quantified by flow cytometry. The high-risk group showed a low activation profile in T cells with lower percentage of CD4+CD38+ (p=0.002), CD4+HLADR-CD38+ (p=0.027) and CD4+Ki67+ T cells (p=0.048). Likewise, this group had a higher percentage of CD4+HLADR-CD38- cells (p=0.013). Although it was not statistically significant, there was a tendency in the high-risk group to present a lower percentage of CD8+HLA-DR+CD38+ (p=0.058). No differences were found in the expression of CD69. To identify whether the high-risk group exhibit differences in the basal levels of plasmatic cytokines and soluble factors, the concentrations of IL-6, IL-8 IL-10, IL-12p70, and TNF-α were quantified by CBA, and the mRNA expression of Elafin, Serpin A1, MIP1-β, RANTES, IL-1β, IL-18, IL-22, Caspase 1, and FoxP3, in PBMCs through qPCR. Compared with the low-risk group, the MSM in the high-risk group exhibit higher mRNA levels of Serpin A1 (p=0.018) and a tendency to express more MIP1-β (p=0.06). No differences were found regards the other soluble factors evaluated. The intracellular expression of Granzyme B, MIP1-β, TNF-α, and IFN-γ by CD4+ and CD8+ T cells was measured after stimulus with a pool of peptides from HIV-1 subtype B consensus Gag or SEB. Likewise, the levels of IL-10, IL-12, IL-1b, IL-6, IL-8, and TNF-α in the culture’s supernatants were quantified by CBA. All the 60 MSM showed a strong specific response to SEB, however, the HIV-1 specific response only was detected in some subjects and there was not a defined pattern of response by risk group. No differences were found in the magnitude nor index of T cell polyfunctionality between the MSM groups in response to HIV-1 Gag peptides. Finally, no statistical differences were found between the groups in the levels of IL-10, IL-12, IL-1β IL-6, IL-8, and TNF-α in the supernatants of HIV-1 stimulated cells. To explore the different NK cell subpopulations in both MSM groups, the CD56 and CD16 expression was analyzed in the CD3- cells from fresh peripheral blood. Both groups of MSM showed a similar distribution of NK cell subpopulations. Then, the expression of IFN-γ, Perforin, Granzyme B, and NKG2D was assessed in total NK cells from PBMCs after being stimulated for 48 hours with the combination of IL-12 and IL-15. The high-risk group showed a lower percentage of total NK cells expressing NKG2D (p=0.021). No differences were found in the magnitude nor polyfunctional index in those cells. To explore the macroscopic and microscopic state of anal mucosal tissue and the expression of the antiviral genes HPN1, HBD2, HBD3, SLPI, RNAse7, TRIM5α, and APOBE3G, an anal sampling was made. In both groups, most MSM presented no symptoms, a healthy anus, and a low frequency of intraepithelial lessons. No statistical differences were found regarding symptoms or the macro and microscopic state of anal mucosa between both groups. Quantification of the mRNA expression of the antiviral genes was no possible due to the low quantity of mRNA obtained, so a qualitative comparison of the detected genes was made between both groups. There were no statistical differences in the detection of the antiviral genes HPN1, HBD2, HBD3, SLPI, RNAse7, TRIM5α, and APOBE3G. In this study, we managed to reach a population with very difficult access given the conditions of the vulnerability of the LGBTIQ+ population in our country and the inclusion criteria that directed the recruitment of individuals with high-risk sexual behaviors in the absence of sex work. The results of this study show that MSM individuals included in the high-risk group have higher-risk sexual behavior than previously reported associated with seroconversion in international MSM cohorts, which demonstrates their high probability of exposure to HIV. Significant differences were found between the groups of high and low risk of exposure concerning sexual behaviors and the immunological factors that have been previously associated with resistance to HIV-1 and that limit its transmission/acquisition. Despite we did not find statistically significant differences between the groups of MSM in all the immunological variables evaluated, it is interesting that the group of individuals who presented extremely risky sexual behaviors, presented, too, a low activation profile of T cells. The lower activation profile of T cells has been described previously in some HESN, which have low expression of T cell activation markers and higher percentages of Treg cells. The study of Camara et al. shows that HESN from serodiscordant couples of Senegal have lower levels of CD38 expression on CD4+T cells than control subjects. This same low expression of CD38 by CD4Tcells has been described in MSM HESN from the Amsterdam cohort, in HESN individuals of serodiscordant couples from the Central African Republic, as well as in HESN from the female sex workers of the Pumwani cohort in Kenya. Moreover, it has been described that T cells with low expression of activation molecules have a lower susceptibility of infection in vitro with HIV-1, and the persistent HIV-1 seronegative status is associated with lower T Cell activation. To our knowledge, this is the first report of a sociodemographic, sexual and immunological characterization of a Colombian cohort of HIV seronegative MSM. Taken together, our results suggest that the protection against the HIV-1 infection in the studied MSM is mediated by a combination of factors/processes: (1) A quiescent immune profile with low basal activation but also a fully functional capacity of CD4+ T cells and NK cells. (2) A protection exerted by HLA-B*18 through the presentation of essential antigens for the HIV-1 viral cycle, leading to a highly efficient specific CTL response by CD8+ cells. (3) The protection led by the HLA-B*18 is, in turn, complemented by the low frequency of HLA-B*35 alleles which are known to recognize and present a reduced repertoire of peptides and are associated with HIV-1 susceptibility. (4) A high responsiveness capacity of NK cells drove by the inhibitory KIR genes/AA haplotype, due to the lower threshold of activation and a stronger response that is exhibited by the NK cells that are licensed by this type of KIRs. Finally (5), A protective anti-viral effect (direct and indirect) by the Serpin A1. It is necessary to continue the study of MSM in high risk of exposure to HIV-1 to better understand their natural response to the virus and improve the prevention and therapy strategies against HIV-1.